Analisis Pengaruh Bauran Promosi (Promotional Mix) Terhadap Intensitas Pembelian Pelanggan Pada PT. GFC Terpadu Plaza Mulia Samarinda - Adisthy Shabrina Nurqamarani 3, Tiara Oktaria Andriati 1, Eddy Soegiarto2 (EKONOMIA, 2021)
The purpose of this study is : 1). To explain the effect of the advertising on customer purcase intensity on PT. GFC Terpadu. 2). To explain the effect of the sales promotion on customer purcase intensity on PT. GFC Terpadu. 3). To explain the effect of the personal selling on customer purcase intensity on PT. GFC Terpadu. 4). To explain the effect of the public relation on customer purcase intensity on PT. GFC Terpadu. 5). To explain the effect of the direct marketing on customer purcase intensity on PT. GFC Terpadu. 6). To explain the effect of the advertising, sales promotions, personal selling, public relation, and direct marketing, simultaneously towards the intensity of customer purchases on PT. GFC Terpadu.The results of this study shows : 1). Advertising variable do not significantly influence for purchase intensity at PT. GFC Terpadu Plaza Mulia Samarinda. 2). Sales promotion variable significantly influence for purchase intensity at PT. GFC Terpadu Plaza Mulia Samarinda. 3). Personal selling variable do not significantly influence for purchase intensity at PT. GFC Terpadu Plaza Mulia Samarinda. 4). Public relation variable significantly influence for purchase intensity at PT. GFC Terpadu Plaza Mulia Samarinda. 5). Direct marketing variable do not significantly influence for purchase intensity at PT. GFC Terpadu Plaza Mulia Samarinda. 6). The variables of advertising, sales promotion, personal selling, public relation, and direct marketing simultaneously affects purchasing intensity at PT. GFC Terpadu Plaza Mulia Samarinda.